Détermination De L’orientation Optimale D’un Bâtiment En Géobéton En Côte d’Ivoire - Tanoe Koffi Fernandez; Gbaha Prosper; Ekoun Magloire (European Scientific Journal, ESJ, 2018)
The objective of this research is to evaluate the impact of the orientation of a building, built in clay brick, on the temperatures of its faces, to determine the best orientation that maximizes building ventilation and minimizes overheating. We first performed a climate analysis of the site using the consultant climate software, then we have evaluate the temperatures of each face using a dynamic thermal simulation. The analysis indicates that in order to benefit from good ventilation, the building should be oriented along the Southwest face; and that an orientation along the South face would reduce the exposure of the building to sunshine. Also, numerical evaluation shows an overheating of about 4° C between the South and North faces; and about 2° C between the East and West faces. In addition, the South, North, East and West faces reach maximum temperatures of 34.75° C, 38.5° C, 40.25° C and 42° C respectively. The choice of an orientation can induce overheating from the wall, up to 7.25° C. A joint analysis of these two results leads to the conclusion that the best orientation for a building in Côte d'Ivoire is the South direction.